Introduction: On-Farm Genetic Resources and Economic Change - Smale, Melinda; King, Amanda (International Food Policy Research Institute, 2005)
The research on which the briefs are based has been published as a collection of case studies geared toward agricultural and resource economists, applied researchers working in international and national organizations, and scientists involved in local plant breeding and genetics (Smale, 2006).